Stabilisation and solidification of contaminated soil using cement and sugarcane bagasse ash (SCBA) - Mohammad Azmi, Mohamad Azim (2018)
Soil that is contaminated with heavy metals has become a major issue worldwide. However, proper remediation techniques such as stabilisation/solidification (S/S) method can be employed and is capable of controlling these heavy metals. Conventionally, the common S/S method used cement as binder on remediating the contaminated soil particularly heavy metals. This research is to investigate the effect of physical and leachability of contaminated soil in S/S method when Sugarcane Bagasse Ash (SCBA) is added to remedy contaminated soil. Landfill contaminated soil was used to test the effectiveness of those binder. Cement was added at a proportion of 5%, 10%, 15% and 20% in sample weights without SCBA while in another sample; the cement was replaced by SCBA at a proportion of 2.5%, 5%, 7.5% and 10%. All samples are to be allowed to harden and cured at room temperature for 7, 14 and 28 days. The effectiveness of the treatment was assessing by conducting physical testing such as Unconfined Compression Strength, Water Absorption and Permeability test. In addition, leaching tests were performed to identify the leachate behavior of heavy metals during treatment. Three leaching tests were conducted and they were the Toxicity Characteristic Leaching Procedure (TCLP), Synthetic Precipitation Leaching Procedure (SPLP) and Dynamic Leaching Test (DLT). Through the physical testing, samples containing 10% OPC mixed with 10% SCBA were found to improve the compressive strength, reduced the water absorption and water permeability measuring 1550 MPa, 17.94% and 4.41 x 10 -10 m/s respectively. In the same way, through the statistical analysis, the R-squared for UCS with respect to mixed design is high at 98%. However, the value for both water absorption and permeability recorded to be marginally low, compared to the value for strength at 89% and 88% respectively. Through the TCLP and SPLP test, results indicated that when SCBA added to OPC content in soil samples, less heavy metal been leached out from the S/S sample. In average, the satisfying result was shown by samples containing 10% OPC + 10% SCBA where reduction of heavy metals in final leachate is more than 90% for As, Cd, Cr, Pb and Zn. Through the Dynamic Leaching Test, sample containing 10% OPC +10% SCBA showed the satisfactory leachability index (Lx) at 9.17, 9.17, 8.81, 8.17 and 6.97 for As, Cd, Cr, Pb and Zn respectively. This indicates that the use of cement and SCBA as a binder was successful in remediating the contaminated soils through the S/S method.